Images of wood : Aspects of the history of sculpture in 20th-Century South Afrika - Rankin, Elizabeth; Dell, Elizabeth; Meintjes, Julia (Johannesburg : Johannesburg Art Gallery, 1989)
Davies, Roger Henry Daller ; Du Toit, Guy Pierre ; Disner, Solly ; Ferreira, Angela Maria ; Harrs, Hannes ; Kelleher, Alison ; Kottler, Moses ; Lea, Philippa Ruth Delisle ; Mabasa, Noria ; Mabaso, Richard Mzamane ; Maurice, Louis ; Miller, Dianne Fay ; Mokoena, Saint ; Nell, Josua Andries ; Noosi, Joel ; Pfaff, Uwe ; Prins, Nico ; Risi, Stephen ; etc.
Images of wood : Aspects of the history of sculpture in 20th-Century South Afrika, Johannesburg Art Gallery, Johannesburg, 1989
boek
Keywords: Afrika; Zuid Afrika